Provisão de Sinistros: Estudo de uma Companhia de Seguros e o Impacto do Fator Cauda - Martinho, Beatriz Sáinz Dinis Raposo (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management